Vancomycin Loading Doses: A Systematic Review. (May 2015) - Reardon, Jillian; Lau, Tim T. Y.; Ensom, Mary H. H.
Objective: To systematically assess the literature to ascertain the pharmacokinetics, pharmacodynamics, and clinical efficacy and safety associated with administration of a vancomycin loading dose (LD).Data Sources: MEDLINE (1948-December 31, 2014), EMBASE (1980-December 31, 2014), Cochrane Central Register of Controlled Trials, International Pharmaceutical Abstracts (1970-December 31, 2014), Google and Google Scholar, and International Clinical Trials Registry Platform were searched using the following terms: vancomycin, glycopeptides, loading dose, dose-response relationship .Study Selection and Data Extraction: Pharmacokinetic, pharmacodynamic, and clinical efficacy studies using vancomycin LDs to achieve trough concentrations of 15 to 20 mg/L were included. Nonhuman, non-English, oral vancomycin, and dialysis patient studies were excluded. Abstracts were included. Study quality was ranked using US Preventative Services Task Force 1996 classification system. Data on study design, baseline characteristics, exclusion criteria, dosing, study outcomes, and conclusions were extracted.Data Synthesis: A total of 8 studies (5 manuscripts [2 level I, 3 level II-3] and 3 abstracts) were cited. Of 6 adult studies, 4 concluded that administration of vancomycin LDs resulted in significantly more patients achieving troughs of 15 to 20 mg/L. Studies in children found that LDs did not lead to rapid attainment of vancomycin levels ≥15 mg/L. No studies assessed clinical or microbiological outcomes. Limitations included heterogeneity and inconsistent timing of concentration measurements.Conclusions: High-quality data to guide the use of vancomycin LDs are lacking. LDs may more rapidly attain vancomycin troughs of 15 to 20 mg/L in adults, but information in pediatrics, obesity, and renal impairment is limited. Further studies are required to determine benefit of LDs on clinical and microbiological outcomes.